PENERAPAN METODE ROLE PLAYING DALAM PEMBELAJARAN SEJARAH UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS XI SMA NEGERI 5 PROVINSI MALUKU UTARA - Zulkifli, Zulkifli; Tomagola, Leny MS (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
This study aims to describe the application of the role-playing method in history learning to increase the learning interest of eleventh-grade students at SMA 5 in North Maluku Province. The problem underlying this research is the low interest of students in participating in history learning, indicated by a lack of attention, motivation, and active participation during the teaching and learning process. This study uses a qualitative approach with a descriptive research type, with the research subjects being history teachers and eleventh-grade students at SMA 5 in North Maluku Province. Data were collected through observation, interviews, and documentation, and then analysed through data reduction, data presentation, and drawing conclusions. The results of the study show that the application of the role-playing method can increase students' interest in learning.It can be seen from the increased enthusiasm of students, their active involvement in discussions and role-playing, as well as their sense of responsibility in performing their respective roles. The classroom atmosphere becomes livelier, more enjoyable, and interactive. The challenges faced include limited time, students' mastery of the material, and some students lacking confidence. However, these challenges can be overcome through teacher guidance and the allocation of roles according to students' abilities.